Three dimensional coastline deformation from insar envisat satellite data - Marghany, Maged Mahmoud (2013)
The paper is focused on three-dimensional (3-D) coastline deformation from interferometry synthetic aperture radar (InSAR). In doing so, conventional InSAR procedures are implemented to three repeat passes of ENVISAT ASAR data. Further, three-dimensional sorting reliabilities algorithm (3D-SRA) is implemented with phase unwrapping technique. Consequently, the 3D-SRA is used to eliminate the phase decorrelation impact from the interferograms. The study shows the performance of InSAR method using the 3D-SRA is better than InSAR procedure which is validated by a lower range of error (0.06±0.32 m) with 90% confidence intervals. In conclusion, integration of the 3D-SRA with phase unwrapping produce accurate 3-D coastline deformation.